Election Night at Bruce Bronzan State Assembly Campaign Headquarters in Roos-Atkins Building - Watkins, Howard::::::::: (1978)
Supporters applauding Linda Bronzan: Mark Wall (blue shirt), Jackie Estes (in pink),? Linda Bronzan, Janice Westerling, Randy Walsh (flowery shirt), Bill Carlson, Janet Ferrar (white dress), Doug Jones, Sandy Walsh, Tony Correia, ??